The Discrimination against Women Reflected in Novels Entrok, Maryam, And Pasung Jiwa by Okky Madasari - Sumarah - Suryaningrum; Sarwiji Suwandi; Herman J Waluyo (Lingua Cultura, 2019)
This research aimed to find out the discrimination against women in Indonesia, especially reflected in novels Entrok, Maryam, and Pasung Jiwa written by Okky Madasari. Over centuries, women in Indonesia had faced various forms of discrimination that happened because of the strong influence of patriarchal culture, norms, customs, and even religion. That viewpoint then caused men and women to have different roles, both biologically and socially. Women had roles to keep house, family, and children, meanwhile, men had roles to provide for living and protection to the family. The discrimination problem, especially for women, was still the most discussed topic due to the lack of public awareness about women’s roles in community life. This research was a descriptive qualitative research using feminism approach. The data in this research were in the forms of sentences, paragraphs, dialogues, and discourses that reflect discrimination against women. The data analysis technique used in this research was content analysis. The research result shows that there is discrimination towards women in the sectors of economic and social based on the utterances from these three novels by Okky Madasari.